Efficacy and Safety of Osteoporosis Medication in Renal Transplantation: A Systematic Review and Meta-Analysis - Amir Sheikholeslami; Amir Behnam Kharazmi; Tahereh Sabaghian; Mohammad Javad Nasiri (Novelty in Biomedicine)
Background: Osteoporosis is a significant concern, especially for individuals undergoing renal transplantation, as it disrupts bone health and increases the risk of fractures. Interventions for osteoporosis aim to address bone-related challenges in patients with renal transplantation, yet concerns persist regarding both efficacy and potential adverse events.